Combination Effects of Microwave Diathermy and Mulligan Bent Leg: Raise Technique on Myogenic Low Back Pain - Tamsil, Rikham; Anwar, Suharto; Muthiah, St.; Ahmad, Hasnia (PT. Riset Press International, 2024)
Myogenic Low Back Pain, commonly known as lower back pain, is caused by the muscles receiving repeated static loads which cause pain, lower back muscle spasms and limited lumbosacral mobility resulting in decreased functional activity. This research is a pre-experiment with a one group pretest-posttest design, aimed at finding out the effect of a combination of Microwave Diathermy and Mulligan Bent Leg Raise Technique on increasing the functional ability of Myogenic Low Back Pain. This research was carried out at the Physiotherapy Polyclinic at RSUD dr. La Palaloi Maros with a sample of 14 people. Results: Based on the Wilcoxon test analysis, p = 0.001 (p < 0.05), which means that microwave diathermy and Mulligan bent leg raise technique interventions can significantly increase functional activity in myogenic low back pain patients. Providing microwave diathermy and mulligan bent leg raise technique can have a significant effect on increasing functional ability in sufferers of myogenic low back pain.